Customer brand engagement : affection to brand usage intent and moderating effect of brand experience - Hintikka, Anni (2015)
Customer engagement is a relatively new area in the marketing literature and academic research has only shortly studied the nature of customer engagement. Despite the slight research numerous work have recognized the growing attention of customer brand engagement and consequently Marketing Science Institute has listed it as one of its key research priorities. Another important research interest which highly affects to customers satisfaction and loyalty, is brand experience. The indirect effect of brand experience to the relationships between customer brand engagement and its consequences are insufficiently examined and therefore in this study brand experience is used as a moderator factor. This study further experiments the customer brand engagement (CBE) scale developed by Hollebeek, Glynn and Brodie (2014). The study aims to find connections between customer involvement, customer brand engagement, and possible consequences of CBE. Furthermore by using brand experience as a moderator this study gets more specific understanding of customer brand engagement toward Arabia brand. Structural equations modeling is used to examine the causal relationships between different constructs. Results confirmed the positive relationships between customer brand engagement and brand usage intent as well as customer brand engagement and self-brand connection. Moreover it was found that brand experience have a negative effect to the relationship between customer brand engagement and brand usage intent. From managerial perspective this study gained more information of customer –brand relationship and therefore gives tools to firm’s to attain and consolidate their competitive advantage. This study enhance the understanding of customer brand engagement and gives more validation to the CBE scale. And by computing new variable to this scale this study develops a perspective by combining the theories of customer engagement and brand experience.